Optimization of mobile phase for the determination of Esomeprazole and related compounds and investigation of stress degradation by LC–MS. Issue 7 (11th March 2013) - Dong, Qixin; Zhu, Jiajun; Sui, Qiang; Tang, Chao; Wang, Xiaomei; Yu, Yunqiu
<x xml:space="preserve">Abstract</x> In this study, the objective was to investigate the degradation behavior of Esomeprazole under different recommended stress conditions according to International Conference on Harmonization of Technical Requirements for Registration of Pharmaceuticals for Human Use [1] by HPLC. Our research showed that the effect of mobile phase species on separation was significant for the determination of Esomeprazole and its related compounds. Successful separation of the drug from its related impurities and degradation products formed under different stress conditions was achieved using ammonium acetate buffer/ACN by a gradient elution. Compared with phosphate buffer/ACN, ammonium acetate buffer/ACN under same pH and gradient showed a great improvement in resolution due to the change of elution order. The drug was subjected to stress conditions including acidic, alkaline, oxidative, photolytic, and thermal conditions. Extensive degradation occurred in acidic and oxidative conditions, while mild degradation was observed in alkaline and photolytic conditions. Besides, it turned out the drug was extremely stable under thermal condition. The stability‐indicating LC–UV method was validated with respect to linearity, precision, accuracy, specificity, and robustness. The LC–MS method was also adopted for the characterization of degradation products. Based on the m/z values and fragmentation patterns, the degradation pathway of the drug has been proposed.